Laminate for transparent conductive film, transparent conductive film, and method for manufacturing transparent conductive film
The transparent conductive film laminate with a specific cured resin layer composition addresses peeling and heat resistance issues, enabling thin, flexible, and transparent conductive films for applications like organic EL displays.
Patent Information
- Application Number
- JP2022510713
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-27
- Filing Date
- 2021-03-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-03-26
AI Technical Summary
Existing transparent conductive films face issues with polyimide resin layers peeling off poorly from resin sheets, especially when thin, and are difficult to process roll-to-roll, lacking in heat resistance and ease of handling.
A transparent conductive film laminate is developed with a process film and a cured resin layer, where the cured resin layer has a thermal deformation rate of 1.2% or less at 150°C and a thickness of 20 μm or less, using a curable resin composition with a polymer component having a glass transition temperature of 250°C or higher, such as polyimide resin, and a curable monomer to facilitate peeling and heat resistance.
The laminate provides a thin, easily peelable, and highly heat-resistant transparent conductive film with good properties, suitable for applications requiring flexibility and transparency, such as organic EL displays.
Smart Images

Figure 0007603659000009 
Figure 0007603659000010 
Figure 0007603659000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate for a transparent conductive film used for forming a transparent conductive layer, a transparent conductive film using the same, and a method for producing a transparent conductive film. [Background technology]
[0002] Transparent conductive films, in which a transparent conductive layer is formed on the surface of a base film, are used in liquid crystal displays, EL (electroluminescence) displays, EC (electrochromic) displays, solar cells, electromagnetic shielding films for electromagnetic shielding, film sensors such as transparent touch panels, and the like. In the manufacturing process of transparent conductive films, processing is often carried out under harsh conditions involving heating, such as sputtering of metal compounds and subsequent annealing treatment. For this reason, high heat resistance is required for the laminate that serves as the base material on which the transparent conductive layer is formed. It is considered that this problem can be solved by using a laminate that includes a film formed using a highly heat-resistant resin such as a polyimide resin (e.g., a resin with a glass transition temperature of 250°C or higher). Furthermore, in recent years, there has been a demand for reducing the thickness of highly heat-resistant resin films in order to improve transparency and flexibility, reduce weight, and the like.
[0003] For example, Prior Art Document 1 discloses a polyimide resin that is soluble in a solvent and can be used to obtain a highly transparent film by a solution casting method. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2017 / 179367 Summary of the Invention [Problem to be solved by the invention]
[0005] As described in Patent Document 1, when a polyimide resin layer is formed on a glass plate by a solution casting method, the polyimide resin layer can be peeled off from the glass plate relatively easily. However, when a polyimide resin layer is formed on a resin sheet or a resin film by a solution casting method, the formed polyimide resin layer may not be peeled off well from the resin sheet or the resin film, or may not be peeled off at all. This tendency is particularly noticeable when the polyimide film formed by the solution casting method is thin. In addition, there has been a problem that it is difficult to process the polyimide film by roll-to-roll.
[0006] In view of the above problems, the present invention aims to provide a laminate for a transparent conductive film, which is thin and has excellent heat resistance, and allows the processing film to be easily peeled off, and which provides a transparent conductive film having good properties. Another aim of the present invention is to provide a transparent conductive film having good properties, which is thin and has excellent heat resistance, and a method for producing the same. [Means for solving the problem]
[0007] As a result of extensive research into solving the above problems, the inventors discovered that the above problems can be solved by providing a laminate for a transparent conductive film used to form a transparent conductive film, the laminate comprising, in this order, a process film and a cured resin layer, and the cured resin layer having a predetermined thermal deformation rate and thickness, and thus completed the present invention. That is, the present invention provides the following [1] to [9]. [1] A laminate for a transparent conductive film used to form a transparent conductive film, A process film and a cured resin layer are provided in this order, the cured resin layer is a layer made of a cured product of a curable resin composition containing a polymer component (A) and a curable monomer (B), The absolute value of the thermal deformation rate of the cured resin layer due to a temperature increase of 150° C. is 1.2% or less, The thickness of the cured resin layer is 20 μm or less, The casting film has a first surface, which may be provided with a release layer, and a second surface, which is not provided with a release layer; The cured resin layer is formed on a second surface of the casting film. [2] The laminate for a transparent conductive film according to the above [1], wherein the glass transition temperature of the polymer component (A) is 250° C. or higher. [3] The laminate for a transparent conductive film according to the above [1] or [2], wherein the weight average molecular weight of the polymer component (A) is 100,000 or more. [4] The laminate for a transparent conductive film according to any one of the above [1] to [3], wherein the polymer component (A) is a polyimide resin. [5] The laminate for a transparent conductive film according to the above [4], wherein the polyimide resin is soluble in methyl ethyl ketone. [6] The laminate for a transparent conductive film according to the above [4] or [5], wherein the polyimide resin has a fluoro group in the molecule. [7] The laminate for a transparent conductive film according to any one of the above [1] to [6], wherein the cured resin layer has a breaking elongation of 2.5% or more. [8] A transparent conductive film comprising the laminate for a transparent conductive film according to any one of the above [1] to [7], and a transparent conductive layer provided on the cured resin layer of the laminate for a transparent conductive film. [9] A method for producing a transparent conductive film, comprising: forming a conductive material layer on the cured resin layer of the laminate for a transparent conductive film according to any one of the above [1] to [7]; and heating the conductive material layer to 140°C or higher to form a transparent conductive layer. Effect of the Invention
[0008] According to the present invention, it is possible to provide a laminate for a transparent conductive film, which is thin and has excellent heat resistance, and allows easy peeling of the processing film, thereby obtaining a transparent conductive film having good properties. In addition, the present invention can provide a transparent conductive film having good properties, which is thin and has excellent heat resistance, and a method for producing the same. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view showing an example of the configuration of a laminate for a transparent conductive film according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view illustrating an example of a configuration of a transparent conductive film according to an embodiment of the present invention. [Diagram 3] 1A to 1C are process diagrams illustrating an example of a method for producing a laminate for a transparent conductive film. [Figure 4] 1A to 1C are process diagrams illustrating an example of a method for producing a transparent conductive film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In this specification, the expression "XX to YY" means "at least XX and at most YY." In this specification, for example, "(meth)acrylic acid" refers to both "acrylic acid" and "methacrylic acid", and similar terms. Hereinafter, a transparent conductive film laminate according to an embodiment of the present invention will be described.
[0011] 1. Transparent conductive film laminate The transparent conductive film laminate according to the embodiment of the present invention comprises a casting film and a cured resin layer in this order. The cured resin layer is a layer made of a cured product of a curable resin composition containing a polymer component (A) and a curable monomer (B), and has an absolute value of a thermal deformation rate of 1.2% or less due to a temperature rise of 150°C and a thickness of 20 μm or less. The casting film has a first surface, and a release layer may or may not be provided on the first surface. The cured resin layer is formed on a second surface of the casting film opposite to the surface having the release layer, and no release layer is provided on the second surface.
[0012] As a result of intensive research, the present inventors have found the following. (i) By obtaining a cured resin layer from a curable resin composition containing a polymer component (A) and a curable monomer (B), and (ii) by forming the cured resin layer on the surface of the processing film that does not have a release layer, the curable resin composition can be applied well on the processing film, and the cured resin layer can be formed well. In addition, even if the cured resin layer is formed to a thickness of 10 μm or less, the cured resin layer can be easily peeled off from the processing film. In addition, (iii) by making the thermal deformation rate of the cured resin layer by 150 ° C. rise 1.2% or less, the cured resin layer can withstand the heat load when forming a transparent conductive layer on the cured resin layer, and the cured resin layer is prevented from being deformed. As a result, the performance of the transparent conductive layer is suppressed from being deteriorated, and a transparent conductive film having good characteristics is obtained.
[0013] In the following, for ease of understanding, the structures of the layers and films will be described with reference to the drawings and using the symbols shown in the drawings, but the present invention is not limited to the embodiments shown in the drawings. FIG. 1 shows a specific example of the configuration of a laminate for a transparent conductive film according to an embodiment of the present invention. 1(a) shows a laminate 10A for a transparent conductive film having a processing film 1 on one side of a cured resin layer 2. As described below, a transparent conductive layer is provided on the side of the cured resin layer 2 opposite to the side on which the processing film 1 is provided, thereby forming a transparent conductive film. The transparent conductive film laminate 10B shown in Fig. 1(b) has processing films 1A and 1B on both sides of the cured resin layer 2. When providing a transparent conductive layer, one of the processing films 1A and 1B is peeled off and removed. Then, a transparent conductive layer is provided on the exposed surface. In this case, at least one of the casting films 1A and 1B is laminated to the cured resin layer with the second surface facing the cured resin layer.
[0014] 1-1. Cured resin layer The cured resin layer of the transparent conductive film laminate according to the embodiment of the present invention is made of a cured product of a curable resin composition containing a polymer component (A) and a curable monomer (B). The cured resin layer may be a single layer or may include a plurality of laminated layers.
[0015] [Polymer component (A)] The glass transition temperature (Tg) of the polymer component (A) is preferably 250° C. or higher, more preferably 290° C. or higher, and even more preferably 320° C. or higher. When the Tg of the polymer component (A) is 250° C. or higher, sufficient heat resistance is easily imparted to the cured resin layer, and it becomes easier to prevent the cured resin layer from being affected by heating such as annealing treatment and causing deformation when forming the transparent conductive layer. In addition, by setting the Tg of the polymer component (A) to 250°C or higher, it becomes easier to avoid a decrease in heat resistance due to the influence of a polymer generated when a curable composition is prepared together with the curable monomer (B) described later and the curable composition is cured. Here, Tg refers to the temperature at the maximum point of tan δ (loss modulus / storage modulus) obtained by viscoelasticity measurement (measurement in tensile mode in the range of 0 to 250° C. at a frequency of 11 Hz and a heating rate of 3° C. / min).
[0016] The weight average molecular weight (Mw) of the polymer component (A) is preferably 100,000 or more, more preferably 200,000 or more, and is preferably 1,000,000 or less, more preferably 800,000 or less, and even more preferably 500,000 or less. The molecular weight distribution (Mw / Mn) of the polymer component (A) is preferably in the range of 1.0 to 5.0, more preferably 2.0 to 4.5. The weight average molecular weight (Mw) and the molecular weight distribution (Mw / Mn) are values measured by gel permeation chromatography (GPC) in terms of polystyrene. By making the Mw at 100,000 or more, it becomes easier to increase the breaking elongation of the cured resin layer.
[0017] As the polymer component (A), a thermoplastic resin is preferred, and an amorphous thermoplastic resin is more preferred. By using an amorphous thermoplastic resin, it becomes easier to obtain a cured resin layer having excellent optical isotropy, and it becomes easier to obtain a laminate for a transparent conductive film having excellent transparency. In addition, since an amorphous thermoplastic resin is generally easily soluble in an organic solvent, it is possible to efficiently form a cured resin layer by using a solution casting method, as described below. Here, the term "amorphous thermoplastic resin" refers to a thermoplastic resin whose melting point is not observed in differential scanning calorimetry.
[0018] The polymer component (A) is preferably soluble in a general-purpose organic solvent having a low boiling point, such as ethyl acetate, methyl ethyl ketone (MEK), etc. If the polymer component (A) is soluble in a general-purpose organic solvent, it becomes easy to form a cured resin layer by coating.
[0019] Particularly preferred polymer component (A) is an amorphous thermoplastic resin having a Tg of 250° C. or higher, which is soluble in general-purpose organic solvents having a low boiling point, such as ethyl acetate or methyl ethyl ketone.
[0020] From the viewpoint of heat resistance, the polymer component (A) is preferably a thermoplastic resin having a ring structure such as an aromatic ring structure or an alicyclic structure, and more preferably a thermoplastic resin having an aromatic ring structure.
[0021] Specific examples of the polymer component (A) include polyimide resins and polyarylate resins having a Tg of 250° C. or higher. These resins generally have high Tg and excellent heat resistance, and are amorphous thermoplastic resins, so that coating film formation by solution casting is possible. Among these, polyimide resins are preferred because they have high Tg and excellent heat resistance, and are easily obtained as resins that are soluble in general-purpose organic solvents while exhibiting good heat resistance.
[0022] The polyimide resin is not particularly limited as long as it does not impair the effects of the present invention, and examples of the polyimide resin that can be used include aromatic polyimide resins, aromatic (carboxylic acid component)-alicyclic (diamine component) polyimide resins, alicyclic (carboxylic acid component)-aromatic (diamine component) polyimide resins, alicyclic polyimide resins, and fluorinated aromatic polyimide resins. In particular, polyimide resins having a fluoro group in the molecule are preferred.
[0023] Specifically, a polyimide resin obtained by using an aromatic diamine compound and a tetracarboxylic dianhydride, polymerizing the polyamic acid, and carrying out a chemical imidization reaction is preferred.
[0024] As the aromatic diamine compound, any aromatic diamine compound can be used as long as it is soluble in a common solvent (e.g., N,N-dimethylacetamide (DMAC)) and gives a polyimide having a predetermined transparency by reaction with the tetracarboxylic dianhydride used in combination. Specifically, m-phenylenediamine, p-phenylenediamine, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)propane, 2-(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2-(3-aminophenyl)-2-(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 3,4'-bis(3-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenyl)]sulfone, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[ 4-(3-aminophenyl) sulfone, bis[4-(3-aminophenoxy)phenyl] ether, bis[4-(4-aminophenoxy)phenyl] ether, bis[3-(3-aminophenoxy)phenyl] ether, bis[4-(3-aminophenoxy)phenyl] methane, bis[4-(4-aminophenoxy)phenyl] methane, bis[3-(3-aminophenoxy)phenyl] methane, bis[3-(4-aminophenoxy)phenyl] methane, 2,2-bis[4-(3-aminophenoxy)phenyl] propane, 2,2-bis[4 -(4-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3 ,3-hexafluoropropane, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-fluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, and the like.
[0025] These aromatic diamine compounds may be used alone, or two or more kinds of aromatic diamine compounds may be used. From the viewpoint of transparency and heat resistance, preferred aromatic diamine compounds are 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2-(3-aminophenyl)-2-(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3 Examples of aromatic diamine compounds having a fluoro group include aromatic diamine compounds having a fluoro group such as 1,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl. At least one of the aromatic diamine compounds used is preferably an aromatic diamine compound having a fluoro group, and particularly preferably 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl. By using an aromatic diamine compound having a fluoro group, it is easy to obtain transparency, heat resistance, and solubility in a solvent.
[0026] As the tetracarboxylic dianhydride, any tetracarboxylic dianhydride can be used as long as it is soluble in a common solvent (e.g., N,N-dimethylacetamide (DMAC)) and gives a polyimide having a predetermined transparency, as with the aromatic diamine compound. Specific examples include 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride, pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 1,4-hydroquinone dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, and 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride. These tetracarboxylic dianhydrides may be used alone, or two or more kinds of tetracarboxylic dianhydrides may be used. From the viewpoints of transparency, heat resistance, and solubility in solvents, it is preferable to use a tetracarboxylic acid dianhydride having at least one type of fluoro group, such as 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride.
[0027] The polymerization into polyamic acid can be carried out by reacting the aromatic diamine compound with the tetracarboxylic dianhydride while dissolving the resulting polyamic acid in a solvent that the polyamic acid is soluble in. Examples of the solvent used for the polymerization into polyamic acid include N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, and dimethylsulfoxide.
[0028] The polymerization reaction to obtain polyamic acid is preferably carried out in a reaction vessel equipped with a stirrer while stirring. For example, a method of dissolving a predetermined amount of aromatic diamine compound in the above-mentioned solvent, adding tetracarboxylic dianhydride while stirring, and reacting to obtain polyamic acid, a method of dissolving tetracarboxylic dianhydride in a solvent, adding aromatic diamine compound while stirring, and reacting to obtain polyamic acid, and a method of alternately adding aromatic diamine compound and tetracarboxylic dianhydride and reacting to obtain polyamic acid, etc. can be mentioned.
[0029] Although there are no particular limitations on the temperature of the polymerization reaction to form polyamic acid, it is preferably carried out at a temperature of 0 to 70° C., more preferably 10 to 60° C., and further preferably 20 to 50° C. By carrying out the polymerization reaction within the above range, it is possible to obtain a high molecular weight polyamic acid that is less colored and has excellent transparency.
[0030] In addition, the aromatic diamine compound and the tetracarboxylic dianhydride used for polymerization into the polyamic acid are used in roughly equimolar amounts, but in order to control the degree of polymerization of the resulting polyamic acid, it is also possible to change the molar amount of the tetracarboxylic dianhydride / the molar amount of the aromatic diamine compound (molar ratio) in the range of 0.95 to 1.05. The molar ratio of the tetracarboxylic dianhydride to the aromatic diamine compound is preferably in the range of 1.001 to 1.02, more preferably 1.001 to 1.01. By making the tetracarboxylic dianhydride slightly in excess of the aromatic diamine compound in this way, the degree of polymerization of the resulting polyamic acid can be stabilized, and the unit derived from the tetracarboxylic dianhydride can be arranged at the end of the polymer, which results in a polyimide with less coloration and excellent transparency.
[0031] The concentration of the resulting polyamic acid solution is preferably adjusted to an appropriate concentration (for example, about 10 to 30% by mass) so as to maintain the viscosity of the solution at an appropriate level and to facilitate handling in the subsequent steps.
[0032] An imidizing agent is added to the obtained polyamic acid solution to carry out a chemical imidization reaction. As the imidizing agent, carboxylic acid anhydrides such as acetic anhydride, propionic anhydride, succinic anhydride, phthalic anhydride, and benzoic anhydride can be used, and it is preferable to use acetic anhydride from the viewpoint of cost and ease of removal after the reaction. The equivalent amount of the imidizing agent used is equal to or more than the equivalent amount of the amide bond of the polyamic acid to be subjected to the chemical imidization reaction, and is preferably 1.1 to 5 times, and more preferably 1.5 to 4 times, of the equivalent amount of the amide bond. By using an imidizing agent in a slight excess relative to the amide bond in this way, the imidization reaction can be carried out efficiently even at a relatively low temperature.
[0033] In the chemical imidization reaction, an aliphatic, aromatic or heterocyclic tertiary amine such as pyridine, picoline, quinoline, isoquinoline, trimethylamine, triethylamine, etc. can be used as an imidization accelerator. By using such amines, the imidization reaction can be efficiently carried out at a low temperature, and as a result, coloring during the imidization reaction can be suppressed, making it easier to obtain a more transparent polyimide.
[0034] There are no particular restrictions on the temperature of the chemical imidization reaction, but it is preferably carried out at 10° C. or more and less than 50° C., and more preferably at 15° C. or more and less than 45° C. By carrying out the chemical imidization reaction at a temperature of 10° C. or more and less than 50° C., coloring during the imidization reaction can be suppressed, and a polyimide with excellent transparency can be obtained.
[0035] Thereafter, if necessary, a poor solvent for polyimide is added to the polyimide solution obtained by the chemical imidization reaction to precipitate the polyimide into powder, followed by drying.
[0036] The polyimide resin is preferably soluble in a low-boiling organic solvent such as ethyl acetate or methyl ethyl ketone. In particular, it is preferably soluble in methyl ethyl ketone. If the polyimide resin is soluble in methyl ethyl ketone, a layer of the curable resin composition can be easily formed by coating and drying.
[0037] A polyimide resin containing a fluoro group is particularly preferred from the viewpoint that it is easily dissolved in a general-purpose organic solvent having a low boiling point, such as methyl ethyl ketone, and therefore it is easy to form a cured resin layer by a coating method. The polyimide resin having a fluoro group is preferably an aromatic polyimide resin having a fluoro group in the molecule, and more preferably has a skeleton represented by the following chemical formula in the molecule. [ka]
[0038] The polyimide resin having the skeleton represented by the above chemical formula has an extremely high Tg exceeding 300°C due to the high rigidity of the skeleton. This can greatly improve the heat resistance of the cured resin layer. In addition, the skeleton is linear and relatively flexible, which makes it easier to increase the breaking elongation of the cured resin layer. Furthermore, the polyimide resin having the above skeleton can be dissolved in a general-purpose organic solvent with a low boiling point, such as methyl ethyl ketone, due to the presence of a fluoro group. Therefore, the coating can be performed using a solution casting method to form a cured resin layer as a coating film, and the solvent can be easily removed by drying. The polyimide resin having the skeleton represented by the above chemical formula can be obtained by polymerization and imidization of the above-mentioned polyamic acid using 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl and 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride.
[0039] The polyarylate resin is a resin made of a polymer compound obtained by the reaction of an aromatic diol with an aromatic dicarboxylic acid or its chloride. The polyarylate resin also has a relatively high Tg and relatively good elongation properties. The polyarylate resin is not particularly limited, and any known polyarylate resin can be used.
[0040] Examples of aromatic diols include bis(hydroxyphenyl)alkanes such as bis(4-hydroxyphenyl)methane (bisphenol F), bis(3-methyl-4-hydroxyphenyl)methane, 1,1-bis(4'-hydroxyphenyl)ethane, 1,1-bis(3'-methyl-4'-hydroxyphenyl)ethane, 2,2-bis(4'-hydroxyphenyl)propane (bisphenol A), 2,2-bis(3'-methyl-4'-hydroxyphenyl)propane, 2,2-bis(4'-hydroxyphenyl)butane, and 2,2-bis(4'-hydroxyphenyl)octane; and bis(hydroxyphenyl)cycloalkanes such as 1,1-bis(4'-hydroxyphenyl)cyclopentane, 1,1-bis(4'-hydroxyphenyl)cyclohexane (bisphenol Z), and 1,1-bis(4'-hydroxyphenyl)-3,3,5-trimethylcyclohexane.Bis(4-hydroxyphenyl)phenylmethane, bis(3-methyl-4-hydroxyphenyl)phenylmethane, bis(2,6-dimethyl-4-hydroxyphenyl)phenylmethane, bis(2,3,6-trimethyl-4-hydroxyphenyl)phenylmethane, bis(3-t-butyl-4-hydroxyphenyl)phenylmethane, bis(3-phenyl-4-hydroxyphenyl)phenylmethane, bis(3-fluoro-4-hydroxyphenyl)phenylmethane, bis(3-bromo-4-hydroxyphenyl)phenyl Methane, bis(4-hydroxyphenyl)-4-fluorophenylmethane, bis(3-fluoro-4-hydroxyphenyl)-4-fluorophenylmethane, bis(4-hydroxyphenyl)-4-chlorophenylmethane, bis(4-hydroxyphenyl)-4-bromophenylmethane, bis(3,5-dimethyl-4-hydroxyphenyl)-4-fluorophenylmethane, 1,1-bis(4'-hydroxyphenyl)-1-phenylethane [bisphenol P], 1,1-bis(3'-methyl-4'-hydroxyphenyl )-1-phenylethane, 1,1-bis(3'-t-butyl-4'-hydroxyphenyl)-1-phenylethane, 1,1-bis(3'-phenyl-4'-hydroxyphenyl)-1-phenylethane, 1,1-bis(4'-hydroxyphenyl)-1-(4'-nitrophenyl)ethane, 1,1-bis(3'-bromo-4'-hydroxyphenyl)-1-phenylethane, 1,1-bis(4'-hydroxyphenyl)-1-phenylpropane, bis(4-hydroxyphenyl)diphenylmethane, bis(4-hydroxyphenyl)diphenylmethane, bis(hydroxyphenyl)phenylalkanes such as bis(4-hydroxyphenyl)dibenzylmethane; bis(hydroxyphenyl)ethers such as bis(4-hydroxyphenyl)ether, bis(3-methyl-4-hydroxyphenyl)ether; bis(hydroxyphenyl)ketones such as bis(4-hydroxyphenyl)ketone, bis(3-methyl-4-hydroxyphenyl)ketone; bis(hydroxyphenyl)sulfides such as bis(4-hydroxyphenyl)sulfide, bis(3-methyl-4-hydroxyphenyl)sulfide;Examples of such bis(hydroxyphenyl)sulfoxides include bis(4-hydroxyphenyl)sulfoxide and bis(3-methyl-4-hydroxyphenyl)sulfoxide; bis(hydroxyphenyl)sulfones such as bis(4-hydroxyphenyl)sulfone [bisphenol S] and bis(3-methyl-4-hydroxyphenyl)sulfone; and bis(hydroxyphenyl)fluorenes such as 9,9-bis(4'-hydroxyphenyl)fluorene and 9,9-bis(3'-methyl-4'-hydroxyphenyl)fluorene.
[0041] Examples of aromatic dicarboxylic acids or their chlorides include phthalic acid, isophthalic acid, terephthalic acid, 4,4'-biphenyldicarboxylic acid, diphenoxyethanedicarboxylic acid, diphenyl ether 4,4'-dicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and their chlorides. The polyarylate resin used may be a modified polyarylate resin. Among these, the polyarylate resin is preferably a resin made of a polymer compound obtained by reacting 2,2-bis(4'-hydroxyphenyl)propane with isophthalic acid.
[0042] The polymer component (A) may be used alone or in combination of two or more. The polymer component (A) may be a combination of a polymer component (A') having a glass transition temperature of 250°C or higher and a polymer component (A") having a glass transition temperature of less than 250°C. Examples of the polymer component (A") include polyamide resins and polyarylate resins having a Tg of less than 250°C, with polyamide resins being preferred.
[0043] The polyamide resin is preferably one that is soluble in an organic solvent, and is preferably a rubber-modified polyamide resin, such as that described in JP-A-2004-035638.
[0044] As the polymer component (A) and the polymer component (A"), those using a single type of polyimide resin, those using a plurality of different types of polyimide resins, and those having at least one of a polyamide resin and a polyarylate resin added to a polyimide resin are preferred from the viewpoint of adjusting the elongation properties and from the viewpoint of solvent resistance.
[0045] When a polyamide resin or a polyarylate resin having a Tg of less than 250° C. is added to a polyimide resin, the amount of the resin added is, from the viewpoint of imparting appropriate flexibility while maintaining a high Tg, preferably 100 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 50 parts by mass or less, and even more preferably 30 parts by mass or less, relative to 100 parts by mass of the polyimide resin, and is preferably 1 part by mass or more, and more preferably 3 parts by mass or more.
[0046] [Curable monomer (B)] The curable monomer (B) is a monomer having a polymerizable unsaturated bond, and is a monomer that can participate in a polymerization reaction or a polymerization reaction. By using the curable monomer (B), the cured resin layer can be easily peeled off from the process film. In addition, a laminate for a transparent conductive film having excellent solvent resistance can be obtained. By forming the cured resin layer as a layer made of a cured product of the curable resin composition containing the above-mentioned polymer component (A) and the above-mentioned curable monomer (B), it becomes easy to form a thin cured resin layer with excellent heat resistance. In addition, by using such a material, optical problems caused by materials having anisotropic molecular orientation such as polyester-based films generally used as substrates for transparent conductive film laminates do not occur. In addition, since the absolute value of the thermal deformation rate of the cured resin layer due to a temperature rise of 150°C is 1.2% or less, the cured resin layer exhibits heat resistance, and therefore, when a transparent conductive layer is formed by heating a conductive material layer, the performance of the transparent conductive layer is prevented from being reduced due to deformation of the cured resin layer due to heating. Furthermore, according to the study by the present inventors, when a resin layer is formed by dissolving only a polyimide resin in a solvent without using a curable monomer (B), applying and drying the resin layer on a release film made of a silicone resin, which is a common release film, the haze tends to increase due to the influence of the unevenness present on the release film surface. In contrast, by using a curable monomer (B) in combination, even if a cured resin layer is provided on the second surface of a process film that does not have a release layer, the cured resin layer can be easily peeled off, so that the increase in haze can be suppressed.
[0047] The molecular weight of the curable monomer (B) is usually 3,000 or less, preferably 200 to 2,000, and more preferably 200 to 1,000. When the molecular weight of the curable monomer (B) is within such a range, the skinning phenomenon described below can be more efficiently suppressed when a coating film of the curable resin composition is formed. The number of polymerizable unsaturated bonds in the curable monomer (B) is not particularly limited. The curable monomer (B) may be a monofunctional monomer having one polymerizable unsaturated bond, or a multifunctional monomer having a plurality of polymerizable unsaturated bonds, such as a bifunctional or trifunctional monomer.
[0048] The monofunctional monomer includes a monofunctional (meth)acrylic acid derivative. The monofunctional (meth)acrylic acid derivative is not particularly limited, and known compounds can be used. For example, monofunctional (meth)acrylic acid derivatives having a nitrogen atom, monofunctional (meth)acrylic acid derivatives having an alicyclic structure, monofunctional (meth)acrylic acid derivatives having a polyether structure, etc. can be mentioned.
[0049] Examples of the monofunctional (meth)acrylic acid derivative having a nitrogen atom include compounds represented by the following formula.
[0050] [ka]
[0051] In the formula, R 1represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; R 2 and R 3 each independently represents a hydrogen atom or an organic group having 1 to 12 carbon atoms; R 2 and R 3 may be bonded to form a ring structure, R 4 represents a divalent organic group. R 1 Examples of the alkyl group having 1 to 6 carbon atoms represented by the formula (I) include a methyl group, an ethyl group, and a propyl group, and a methyl group is preferable. R 2 and R 3 Examples of the organic group having 1 to 12 carbon atoms represented by the formula (I) include alkyl groups having 1 to 12 carbon atoms, such as methyl, ethyl, and propyl groups; cycloalkyl groups having 3 to 12 carbon atoms, such as cyclopentyl and cyclohexyl groups; and aromatic groups having 6 to 12 carbon atoms, such as phenyl, biphenyl, and naphthyl groups. These groups may have a substituent at any position. In addition, R 2 and R 3 may be joined together to form a ring, and the ring may further have a nitrogen atom or an oxygen atom in the skeleton. R 4 As the divalent organic group represented by the formula: -(CH 2 ) m -, -NH-(CH 2 ) m In this case, m is an integer of 1 to 10.
[0052] Among these, the monofunctional (meth)acrylic acid derivative having a nitrogen atom is preferably (meth)acryloylmorpholine represented by the following formula:
[0053] [ka]
[0054] By using a monofunctional (meth)acrylic acid derivative having a nitrogen atom as the curable monomer (B), a cured resin layer having better heat resistance can be formed.
[0055] Examples of the monofunctional (meth)acrylic acid derivative having an alicyclic structure include compounds represented by the following formula.
[0056] [ka]
[0057] In the formula, R 1 has the same meaning as above, and R 5 is a group having an alicyclic structure. R 5 Examples of the group having an alicyclic structure represented by the formula (I) include a cyclohexyl group, an isobornyl group, a 1-adamantyl group, a 2-adamantyl group, and a tricyclodecanyl group.
[0058] Specific examples of the monofunctional (meth)acrylic acid derivative having an alicyclic structure include isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, 1-adamantyl (meth)acrylate, and 2-adamantyl (meth)acrylate.
[0059] By using a monofunctional (meth)acrylic acid derivative having an alicyclic structure as the curable monomer (B), a cured resin layer having more excellent optical properties can be formed.
[0060] Examples of the monofunctional (meth)acrylic acid derivative having a polyether structure include compounds represented by the following formula.
[0061] [ka]
[0062] In the formula, R 1 has the same meaning as above, and R 6 R represents an organic group having 1 to 12 carbon atoms. 6Examples of the organic group having 1 to 12 carbon atoms represented by the formula (1) include alkyl groups having 1 to 12 carbon atoms, such as a methyl group, an ethyl group, and a propyl group; cycloalkyl groups having 3 to 12 carbon atoms, such as a cyclohexyl group; aromatic groups having 6 to 12 carbon atoms, such as a phenyl group, a biphenyl group, and a naphthyl group; and the like. j represents an integer of 2 to 20.
[0063] Specific examples of monofunctional (meth)acrylic acid derivatives having a polyether structure include ethoxylated o-phenylphenol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and phenoxypolyethylene glycol (meth)acrylate.
[0064] By using a monofunctional (meth)acrylic acid derivative having a polyether structure as the curable monomer (B), a cured resin layer having excellent toughness can be formed.
[0065] The polyfunctional monomer includes polyfunctional (meth)acrylic acid derivatives. The polyfunctional (meth)acrylic acid derivative is not particularly limited, and known compounds can be used, for example, di- to hexafunctional (meth)acrylic acid derivatives. Examples of the difunctional (meth)acrylic acid derivative include compounds represented by the following formula.
[0066] [ka]
[0067] In the formula, R 1 has the same meaning as above, and R 7 R represents a divalent organic group. 7 Examples of the divalent organic group represented by the formula include groups represented by the following formula:
[0068] [ka]
[0069] (In the formula, s represents an integer of 1 to 20, t represents an integer of 1 to 30, u and v each independently represent an integer of 1 to 30, and "-" at both ends represents a bond.)
[0070] Specific examples of the bifunctional (meth)acrylic acid derivative represented by the above formula include tricyclodecane dimethanol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propoxylated ethoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, 1,10-decane diol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, etc. Among these, from the viewpoint of heat resistance and toughness, tricyclodecane dimethanol di(meth)acrylate and the like, which has R 7 In the above formula, R 7 and 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, etc., in which the divalent organic group represented by R 7 It is preferable that the divalent organic group represented by the following formula has a 9,9-bisphenylfluorene skeleton.
[0071] Other examples of bifunctional (meth)acrylic acid derivatives include neopentyl glycol adipate di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphate di(meth)acrylate, di(acryloxyethyl)isocyanurate, and allylated cyclohexyl di(meth)acrylate.
[0072] Examples of trifunctional (meth)acrylic acid derivatives include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propionic acid modified dipentaerythritol tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, and tris(acryloxyethyl)isocyanurate. An example of the tetrafunctional (meth)acrylic acid derivative is pentaerythritol tetra(meth)acrylate. An example of a pentafunctional (meth)acrylic acid derivative is propionic acid-modified dipentaerythritol penta(meth)acrylate. Examples of the hexafunctional (meth)acrylic acid derivative include dipentaerythritol hexa(meth)acrylate and caprolactone-modified dipentaerythritol hexa(meth)acrylate.
[0073] As the curable monomer (B), a cyclopolymerizable monomer may be used. The cyclopolymerizable monomer is a monomer that has the property of undergoing radical polymerization while cyclizing. Examples of the cyclopolymerizable monomer include non-conjugated dienes, and for example, α-allyloxymethylacrylic acid monomers can be used, and 2-allyloxymethylacrylic acid alkyl esters having 1 to 4 carbon atoms and cyclohexyl 2-(allyloxymethyl)acrylate are preferred, 2-allyloxymethylacrylic acid alkyl esters having 1 to 4 carbon atoms are more preferred, and 2-(allyloxymethyl)methyl acrylate is even more preferred. In addition, cyclopolymerizable monomers such as dimethyl-2,2'-[oxybis(methylene)]bis-2-propenoate, diethyl-2,2'-[oxybis(methylene)]bis-2-propenoate, di(n-propyl)-2,2'-[oxybis(methylene)]bis-2-propenoate, di(i-propyl)-2,2'-[oxybis(methylene)]bis-2-propenoate, di(n-butyl)-2,2'-[oxybis(methylene)]bis-2-propenoate, di(n-hexyl)-2,2'-[oxybis(methylene)]bis-2-propenoate, and dicyclohexyl-2,2'-[oxybis(methylene)]bis-2-propenoate can also be used.
[0074] The curable monomer (B) may be used alone or in combination of two or more. Among these, the curable monomer (B) is preferably a polyfunctional monomer, since it can provide a cured resin layer having excellent heat resistance and solvent resistance. As the polyfunctional monomer, a bifunctional (meth)acrylic acid derivative is preferable, since it is easily mixed with the polymer component (A), and the polymer is less likely to shrink during curing, and curling of the cured product can be suppressed. It is more preferable that the curable monomer (B) contains a polyfunctional (meth)acrylate compound and a cyclopolymerizable monomer. By using them in combination, it is easy to adjust the breaking elongation of the cured resin layer to a predetermined range while appropriately adjusting the heat resistance of the cured resin layer. When the curable monomer (B) contains a polyfunctional monomer, the content thereof is preferably 40 mass % or more, and more preferably 50 to 100 mass %, in the total amount of the curable monomer (B).
[0075] [Curable resin composition] The curable resin composition used to form the cured resin layer according to an embodiment of the present invention can be prepared by mixing the polymer component (A), the curable monomer (B), and, if desired, a polymerization initiator described below and other components, and dissolving or dispersing the mixture in a suitable solvent.
[0076] The total content of the polymer component (A) and the curable monomer (B) in the curable resin composition is preferably 40 to 99.5 mass%, more preferably 60 to 99 mass%, and even more preferably 80 to 98 mass%, based on the total mass of the curable resin composition excluding the solvent.
[0077] The content of the polymer component (A) and the curable monomer (B) in the curable resin composition, in terms of the mass ratio of the polymer component (A) to the curable monomer (B), is preferably polymer component (A):curable monomer (B)=30:70 to 90:10, more preferably 35:65 to 80:20. In the curable resin composition, when the mass ratio of polymer component (A):curable monomer (B) is within this range, the flexibility of the obtained cured resin layer tends to be improved and the solvent resistance of the cured resin layer tends to be maintained.
[0078] In addition, if the content of the curable monomer (B) in the curable resin composition is within the above range, for example, when the cured resin layer is obtained by a solution casting method, the solvent can be removed efficiently, and therefore the problem of deformation such as curling or waving caused by a long drying process can be solved.
[0079] When a combination of multiple resins having different solvent solubilities is used as the polymer component (A), such as a combination of the above-mentioned polyimide resin with a polyamide resin or a polyarylate resin, it is preferable to first dissolve the resins in appropriate solvents, and then add a solution of the other resin to the low-boiling organic solvent in which the resin has been dissolved.
[0080] The curable resin composition may contain a polymerization initiator as desired. The polymerization initiator may be any initiator capable of initiating a curing reaction, and may be, for example, a thermal polymerization initiator or a photopolymerization initiator.
[0081] Examples of the thermal polymerization initiator include organic peroxides and azo compounds. Examples of organic peroxides include dialkyl peroxides such as di-t-butyl peroxide, t-butylcumyl peroxide, and dicumyl peroxide; diacyl peroxides such as acetyl peroxide, lauroyl peroxide, and benzoyl peroxide; ketone peroxides such as methyl ethyl ketone peroxide, cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide; and peroxides such as 1,1-bis(t-butylperoxy)cyclohexane. Examples of the peroxyester include ketals; hydroperoxides such as t-butyl hydroperoxide, cumene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, and 2,5-dimethylhexane-2,5-dihydroperoxide; and peroxyesters such as t-butyl peroxyacetate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxybenzoate, and t-butyl peroxyisopropyl carbonate. Examples of azo compounds include 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, and 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile.
[0082] Photopolymerization initiators include 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-[4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl]-2-methyl-propan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamine, and the like. Alkylphenone-based photopolymerization initiators such as 1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone; phosphorus-based photopolymerization initiators such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, ethyl(2,4,6-trimethylbenzoyl)-phenylphosphineate, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide; bis(η 5-2,4-cyclopentadien-1-yl)-bis[2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl]titanium and other titanocene-based photopolymerization initiators; 1,2-octanedione-1-[4-(phenylthio)-2-(O-benzoyloxime)], ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime) and other oxime ester-based photopolymerization initiators; benzophenone, p-chlorobenzophenone, benzoylbenzoic acid, o-benzoylbenzoic acid methyl, 4-methylbenzophenone, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4-benzoyl benzophenone-based photopolymerization initiators such as 13-acryloyl-4'-methyl-diphenyl sulfide, 3,3'-dimethyl-4-methoxybenzophenone, 2,4,6-trimethylbenzophenone, and 4-(13-acryloyl-1,4,7,10,13-pentaoxatridecyl)-benzophenone; thioxanthone-based photopolymerization initiators such as thioxanthone, 2-chlorothioxanthone, 3-methylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diisopropylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, and 4-isopropylthioxanthone; and the like.
[0083] Among the above photopolymerization initiators, phosphorus-based photopolymerization initiators such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, ethyl(2,4,6-trimethylbenzoyl)-phenylphosphineate, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide are preferred. When the polymer component (A) is a thermoplastic resin having an aromatic ring, the polymer component (A) may absorb ultraviolet light, which may make the curing reaction difficult to occur. However, by using the phosphorus-based photopolymerization initiator, the curing reaction can be efficiently promoted by utilizing light of a wavelength that is not absorbed by the polymer component (A). The polymerization initiators can be used alone or in combination of two or more.
[0084] The content of the polymerization initiator is preferably from 0.05 to 15 mass %, more preferably from 0.05 to 10 mass %, and even more preferably from 0.05 to 5 mass %, based on the total amount of the curable resin composition.
[0085] The curable resin composition may contain a photopolymerization initiator aid such as triisopropanolamine or 4,4'-diethylaminobenzophenone in addition to the polymer component (A), the curable monomer (B), and the polymerization initiator.
[0086] The solvent used in preparing the curable resin composition is not particularly limited, and examples thereof include aliphatic hydrocarbon solvents such as n-hexane and n-heptane; aromatic hydrocarbon solvents such as toluene and xylene; halogenated hydrocarbon solvents such as dichloromethane, ethylene chloride, chloroform, carbon tetrachloride, 1,2-dichloroethane, and monochlorobenzene; alcohol solvents such as methanol, ethanol, propanol, butanol, and propylene glycol monomethyl ether; ketone solvents such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; ester solvents such as ethyl acetate and butyl acetate; cellosolve solvents such as ethyl cellosolve; and ether solvents such as 1,3-dioxolane.
[0087] The content of the solvent in the curable resin composition is not particularly limited, but is usually 0.1 to 1,000 g, preferably 1 to 100 g, per 1 g of the polymer component (A). By appropriately adjusting the amount of the solvent, the viscosity of the curable resin composition can be appropriately adjusted.
[0088] The curable resin composition may further contain known additives such as a plasticizer, an antioxidant, and an ultraviolet absorber, within the scope of not impairing the object and effect of the present invention.
[0089] The method for curing the curable resin composition can be appropriately determined depending on the type of polymerization initiator and curable monomer used, and will be described in detail in the section on the method for producing a laminate for a transparent conductive film described later.
[0090] [Properties of the cured resin layer] The thickness of the cured resin layer is 20 μm or less, preferably 15 μm or less, more preferably 12 μm or less, and even more preferably 10 μm or less. There is no particular lower limit to the thickness of the cured resin layer, but it is usually 0.1 μm or more, preferably 0.2 μm or more.
[0091] When the thickness of the cured resin layer is 20 μm or less, a thin and lightweight laminate for forming a transparent conductive film can be easily obtained, and the laminate for forming a transparent conductive film can have excellent handleability. In addition, since the cured resin layer is thin, a transparent conductive film that is highly transparent and thin and lightweight can be obtained. Therefore, in applications such as organic EL displays that require thinness, the transparent conductive film is preferable because it does not increase the overall thickness of the applied device. In addition, a thin transparent conductive film can improve the flexibility and bending resistance of the transparent conductive film after mounting.
[0092] As described above, the cured resin layer of the laminate for forming a transparent conductive film according to the embodiment of the present invention has an absolute value of thermal deformation rate of 1.2% or less due to a temperature rise of 150° C. Therefore, it has excellent heat resistance, and can be made into a laminate for forming a transparent conductive film having excellent heat resistance. In particular, even if a laminate for forming a transparent conductive film is produced through a process involving heating after the formation of a cured resin layer, such as forming a conductive material layer on a cured resin layer by sputtering, deposition, coating, etc., and then heating the conductive material layer to form a transparent conductive layer, problems are unlikely to occur because the cured resin layer has high heat resistance. Specifically, it is possible to avoid a situation in which the transparent conductive layer cannot be formed well or the transparent conductive layer cannot exhibit sufficient electrical properties due to deformation of the cured resin layer, etc. From the same viewpoint, it is preferable that the absolute value of the thermal deformation rate of the cured resin layer due to a temperature rise of 150°C is 0.8% or less. The thermal deformation rate of the cured resin layer is a characteristic value measured by the method described in the examples below. In the examples, the thickness of the cured resin layer is adjusted to 20 μm for measurement, but in order to avoid a problem that the cured resin layer is thin and stretched when attached to a jig of a thermomechanical analyzer, the cured resin layer is laminated to a thickness of 20 μm or more for measurement.
[0093] As described later, from the viewpoint of being able to easily form a cured resin layer by curing a coating film obtained by applying a curable resin composition onto a process film, the cured resin layer is preferably a cured product of a coating film of the curable resin composition formed on a surface (second surface) of the process film on which no release layer is provided.
[0094] The cured resin layer also has excellent solvent resistance. Because of its excellent solvent resistance, for example, even when an organic solvent is used to form another layer on the surface of the cured resin layer, the surface of the cured resin layer is hardly dissolved. Therefore, for example, even when a transparent conductive layer is formed on the surface of the cured resin layer by a coating method using a resin solution containing an organic solvent, the components of the cured resin layer are unlikely to be mixed into the transparent conductive layer, so that the electrical properties of the transparent conductive layer are unlikely to be deteriorated.
[0095] From this viewpoint, the gel fraction of the cured resin layer is preferably 90% or more, and more preferably 94% or more. A cured resin layer having a gel fraction of 90% or more has excellent solvent resistance, so that even when an organic solvent is used to form another layer on the surface of the cured resin layer by coating, the surface of the cured resin layer is hardly dissolved, and it is easy to obtain a laminate for a transparent conductive film having excellent solvent resistance.
[0096] Here, the gel fraction is calculated by wrapping a cured resin layer cut to 100 mm x 100 mm in a 150 mm x 150 mm nylon mesh (#120) whose mass has been measured in advance, immersing it in toluene (100 mL) for 3 days, removing it and drying it at 120°C for 1 hour, and then leaving it under conditions of 23°C and 50% relative humidity for 3 hours to adjust the humidity, measuring the mass, and calculating the gel fraction from the following formula.
[0097] Gel fraction (%) = [(mass of remaining resin after immersion) / (mass of resin before immersion)] × 100
[0098] The cured resin layer has excellent interlayer adhesion with the transparent conductive layer, that is, the transparent conductive layer can be formed on the cured resin layer without providing an anchor coat layer.
[0099] The cured resin layer is preferably colorless and transparent. When the cured resin layer is colorless and transparent, the laminate for forming a transparent conductive film according to the embodiment of the present invention can be preferably used for optical applications.
[0100] The cured resin layer has a low birefringence and excellent optical isotropy. The in-plane retardation of the cured resin layer is usually 20 nm or less, and preferably 15 nm or less. The retardation in the thickness direction is usually -500 nm or less, and preferably -450 nm or less. The value obtained by dividing the in-plane retardation by the thickness of the cured resin layer (birefringence) is usually 100 x 10 -5 or less, preferably 20×10 -5 The following is the result. When the in-plane retardation, thickness-direction retardation, and birefringence of the curable resin layer are within the above-mentioned ranges, a laminate for forming a transparent conductive film having low birefringence and excellent optical isotropy can be obtained, and a transparent conductive film produced using this laminate for forming a transparent conductive film can be preferably used for optical applications.
[0101] The breaking elongation of the cured resin layer is preferably 2.5% or more, more preferably 2.6% or more, and even more preferably 2.7% or more. If the breaking elongation of the cured resin layer is 2.5% or more, it becomes easy to adjust the breaking elongation of the laminate for forming a transparent conductive film to about 2% or more, and as a result, it is easy to obtain a laminate for forming a transparent conductive film having excellent flexibility.
[0102] 1-2. Processing film The processing film has the role of protecting the cured resin layer and other layers that are optionally provided as described below when the laminate for forming a transparent conductive film or the transparent conductive film described below is stored, transported, etc., and is peeled off in a specified process. The process film has, for example, a base layer. The process film may have layers other than the base layer, but when a release layer is provided on one surface (first surface) of the process film, the cured resin layer is provided on the surface (second surface) of the process film opposite to the surface on which the release layer is provided. In the above-mentioned Figures 1(a) and 1(b), the first surface of the process film 1, 1A is represented by the symbol S1, and the second surface of the process film 1, 1A is represented by the symbol S2.
[0103] By having the process film, the transparent conductive film laminate can be made into a transparent conductive film laminate with high handleability while protecting the cured resin layer. In addition, when the curable resin composition is applied to the process film, if a peeling layer is provided on the surface of the process film, the coating film may not be uniform. In the manufacturing process of the transparent conductive film laminate according to the embodiment of the present invention, a uniform coating film can be obtained by applying the curable resin composition to the second surface of the process film on which the peeling layer is not provided. The transparent conductive film laminate may have a process film on one side of the cured resin layer as shown in FIG. 1(a), or may have a process film on both sides of the cured resin layer as shown in FIG. 1(b). In the latter case, it is preferable to use two types of process films to make the process film to be peeled first easier to peel. In this case, at least one of the process films 1A and 1B has a second surface without a peeling layer, and a cured resin layer may be formed on that surface. When applying a curable resin composition onto a casting film to form a cured resin layer, it is preferable to form a coating of the curable resin composition on the second surface of the casting film having a second surface, of casting films 1A and 1B, so as to obtain a uniform coating.
[0104] The process film is preferably in the form of a sheet or film. The term "sheet or film" is not limited to long ones, but also includes short flat ones.
[0105] Examples of the base layer of the process film include paper base materials such as glassine paper, coated paper, and fine paper; laminated paper obtained by laminating these paper base materials with thermoplastic resins such as polyethylene and polypropylene; the above paper base materials that have been sealed with cellulose, starch, polyvinyl alcohol, acrylic-styrene resin, and the like; plastic films such as polyester films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, and polyolefin films such as polyethylene and polypropylene; and glass.
[0106] The casting film may also have a release layer, in which case it has a release layer on only one surface (the first surface). The release layer can be formed using a conventionally known release agent such as a silicone-based release agent, a fluorine-based release agent, an alkyd-based release agent, or an olefin-based release agent. The thickness of the release layer is not particularly limited, but is usually 0.02 to 2.0 μm, and more preferably 0.05 to 1.5 μm.
[0107] From the viewpoint of ease of handling, the thickness of the processing film is preferably from 1 to 500 μm, and more preferably from 5 to 300 μm.
[0108] 1-3.Other layers The process film may have layers other than the release layer, such as an easy-adhesion layer or an antistatic layer, but it is preferable that no layers other than the release layer are provided on the second surface on which the release layer is not provided.
[0109] Among the constituent layers of the laminate for transparent conductive film, the portion (separation layer) that is peeled off from the processing film in a predetermined process includes a cured resin layer. The cured resin layer is laminated on the processing film without any other layers, so the cured resin layer is located on one of the outermost surfaces of the separation layer. On the other surface side of the separation layer, an easy-adhesion layer, an antistatic layer, etc. other than the cured resin layer may be provided, but since the separation layer is a layer that constitutes the transparent conductive film after the processing film is removed, it is preferable that the separation layer is thin, and it is preferable that the number and thickness of layers other than the cured resin layer are minimized.
[0110] 2. Transparent conductive film The transparent conductive film according to the embodiment of the present invention includes a processing film, a cured resin layer, and a transparent conductive layer in this order. When the transparent conductive film is actually used, the processing film is peeled off from the transparent conductive film, and the transparent conductive film is incorporated into a display or a solar panel, or is attached to a substrate of a touch sensor for a touch panel. For example, when the transparent conductive film has an adhesive layer as described below, the transparent conductive film is applied to the application portion by attaching the transparent conductive film to the application portion through the adhesive layer, and after attachment, the processing film is peeled off and removed.
[0111] FIG. 2 shows a specific example of the configuration of the transparent conductive film according to the embodiment of the present invention. The transparent conductive film 20 shown in FIG. 2(a) has a transparent conductive layer 3 on one side of a cured resin layer 2, and a processing film 1 on the side of the cured resin layer 2 opposite the transparent conductive layer 3. The transparent conductive layer 3 is formed, for example, so as to cover the entire surface of the cured resin layer 2. The transparent conductive layer 3 can be patterned into a desired shape by an appropriate method such as etching. The transparent conductive film 21 shown in FIG. 2(b) has a patterned transparent conductive layer 31 on one side of the cured resin layer 2. By selectively disposing a transparent conductive material on the cured resin layer 2, the transparent conductive layer 31 having a desired pattern shape may be formed on the cured resin layer 2 without going through a process such as etching. If the process film 1 is peeled off from the transparent conductive film in the state shown in Figure 2, it will be difficult to handle, so it is preferable to peel off and remove the process film 1 after applying the transparent conductive film to an application portion such as an adherend.
[0112] The thickness of the transparent conductive film can be appropriately determined depending on the intended use, etc. From the viewpoint of handleability, the substantial thickness of the transparent conductive film according to the embodiment of the present invention is preferably 0.3 to 50 μm, more preferably 0.5 to 25 μm, and more preferably 0.7 to 12 μm. The term "substantial thickness" refers to the thickness in a used state. That is, although the transparent conductive film has a processing film, the thickness of the part (processing film, etc.) that is removed during use is not included in the "substantial thickness."
[0113] In this specification, the term "transparent" in relation to a transparent conductive film means that the light transmittance at a wavelength of 450 nm is 80% or more.
[0114] The transparent conductive film according to the embodiment of the present invention has a low birefringence and excellent optical isotropy. The in-plane retardation of the transparent conductive film is usually 20 nm or less, and preferably 15 nm or less. The thickness direction retardation is usually -500 nm or less, and preferably -450 nm or less. The value obtained by dividing the in-plane retardation by the thickness of the transparent conductive film (birefringence) is usually 100×10 -5 or less, preferably 20×10 -5 The following is the result. When the in-plane retardation, thickness direction retardation, and birefringence of the transparent conductive film are within the above ranges, the transparent conductive film according to the embodiment of the present invention has excellent optical isotropy and can be preferably used for optical applications.
[0115] Examples of conductive materials constituting the transparent conductive layer include metals, alloys, metal oxides, electrically conductive compounds, and mixtures thereof. Specifically, antimony-doped tin oxide (ATO); fluorine-doped tin oxide (FTO); semiconductive metal oxides such as tin oxide, germanium-doped zinc oxide (GZO), zinc oxide, indium oxide, indium tin oxide (ITO), and indium zinc oxide (IZO); metals such as gold, silver, chromium, and nickel; mixtures of these metals and conductive metal oxides; inorganic conductive substances such as copper iodide and copper sulfide; and organic conductive materials such as polyaniline, polythiophene, and polypyrrole. The transparent conductive layer may be formed by assembling particulate metals such as nanofillers, nanorods, and nanofibers, such as silver.
[0116] The method for forming the transparent conductive layer is not particularly limited. For example, a vapor deposition method, a sputtering method, an ion plating method, a thermal CVD method, a plasma CVD method, etc. may be mentioned. In addition, for example, a coating material containing a particulate metal may be applied to the laminate for a transparent conductive film to obtain a transparent conductive layer from the coating film.
[0117] The thickness of the transparent conductive layer may be appropriately selected depending on the application, etc. It is usually from 10 nm to 50 μm, and preferably from 20 nm to 20 μm.
[0118] The transparent conductive film according to the embodiment of the present invention is not limited to the configuration shown in FIG. 2, and may further contain one or more other layers as long as the object of the present invention is not impaired. Examples of the other layers include an impact absorbing layer, an adhesive layer, etc. The positions of the other layers are not particularly limited.
[0119] The shock absorbing layer is a layer that protects the transparent conductive layer when an impact is applied to the transparent conductive layer. The material for forming the shock absorbing layer is not particularly limited, but examples thereof include acrylic resins, urethane resins, silicone resins, olefin resins, and rubber materials.
[0120] The method for forming the impact absorbing layer is not particularly limited, and examples thereof include a method in which an impact absorbing layer forming solution containing a material for forming the impact absorbing layer and, if desired, other components such as a solvent is applied onto the layer to be laminated, and the resulting coating film is dried and, if necessary, heated to form the impact absorbing layer. Alternatively, the impact absorbing layer may be formed separately on a release substrate, and the obtained film may be transferred onto the layer to be laminated. The thickness of the impact absorbing layer is usually 1 to 100 μm, preferably 5 to 50 μm.
[0121] The adhesive layer is a layer used when attaching the transparent conductive film to an adherend. The material for forming the adhesive layer is not particularly limited, and known adhesives or pressure-sensitive adhesives such as acrylic, silicone, and rubber-based adhesives, heat seal materials, and the like can also be used. In the transparent conductive film, when an adhesive layer is formed on the opposite side of the cured resin layer from the surface facing the process film, a thin coating having a cured resin layer and a transparent conductive layer can be easily formed on the adherend by peeling off the process film after attaching the transparent conductive film laminate to the adherend with the adhesive layer. In the present invention, since the process film is flexible, such attachment can be easily performed, and the process film can also be easily peeled off. The transparent conductive film may have a release film for protecting the adhesive layer on the opposite side of the adhesive layer facing the cured resin layer. As a result, the transparent conductive film has a process film and a release film on the outermost layers on both sides, making it easy to handle.
[0122] 3. Method for manufacturing laminate for forming transparent conductive film The laminate for forming a transparent conductive film according to the embodiment of the present invention is manufactured using a casting film. By using the casting film, the laminate for forming a transparent conductive film can be manufactured efficiently and easily. In particular, a method including the following steps 1 and 2 is preferred.
[0123] Step 1: A step of forming a curable resin layer on a cast film using a curable resin composition containing a polymer component (A) and a curable monomer (B). Step 2: A step of curing the curable resin layer obtained in step 1 to form a cured resin layer.
[0124] An example of a manufacturing process for a laminate for a transparent conductive film according to an embodiment of the present invention is shown in Figure 3. Figure 3(a) shows the state before the formation of the curable resin layer, Figure 3(b) corresponds to the above-mentioned step 1, and Figure 3(c) corresponds to the above-mentioned step 2. In Figures 3(a) to 3(c), similar to Figure 1(a), the first surface of the cast film 1 is represented by the symbol S1, and the second surface of the cast film 1 is represented by the symbol S2.
[0125] (Process 1) First, a curable resin layer (2a in FIG. 3(b)) is formed on the surface (second surface) of a casting film (1 in FIG. 3(a)) using a curable resin composition containing a polymer component (A) and a curable monomer (B). The curable resin layer is preferably formed by coating.
[0126] The method for coating the curable resin composition on the casting film is not particularly limited, and known coating methods such as spin coating, spray coating, bar coating, knife coating, roll coating, blade coating, die coating, gravure coating, etc. can be used. By coating the curable resin composition on the second surface of the casting film, it is easy to obtain a uniform coating film.
[0127] The method for drying the obtained coating film is not particularly limited, and a conventionally known drying method such as hot air drying, hot roll drying, and infrared irradiation can be used. When the polymerizable component (A) is dissolved alone in a solvent to form a resin layer without using the curable monomer (B), the surface of the resin layer is likely to dry first, and the solvent remains inside the resin layer (so-called "skinning"). As described above, the cured resin layer according to the embodiment of the present invention has a small thermal deformation rate, and the polymer component (A) contained in the curable resin composition used to form this cured resin layer generally has a high Tg. In this case, the skinning phenomenon is particularly likely to occur. However, since the curable resin composition contains the curable monomer (B), when the coating film obtained by the solution casting method is dried, the fluidity of the resin composition is maintained, and the solvent can be efficiently removed up to the inside of the resin layer.
[0128] The drying temperature for the coating is usually 30 to 150°C, preferably 50 to 100°C. The thickness of the dried coating film (curable resin layer) is not particularly limited, but since there is almost no difference in thickness from the thickness after curing, the thickness may be the same as the thickness of the curable resin layer described above.
[0129] (Process 2) Next, a cured resin layer is formed by curing the curable resin layer obtained in step 1. This cured resin layer becomes the cured resin layer (reference numeral 2 in FIG. 3(c)). The method for curing the curable resin layer is not particularly limited, and a known method can be used. For example, when the curable resin layer is formed using a curable resin composition containing a thermal polymerization initiator, the curable resin layer can be cured by heating the curable resin layer. The heating temperature is usually 30 to 150°C, preferably 50 to 100°C.
[0130] In addition, when the curable resin layer is formed using a curable resin composition containing a photopolymerization initiator, the curable resin layer can be cured by irradiating the curable resin layer with active energy rays. The active energy rays can be irradiated using a high-pressure mercury lamp, an electrodeless lamp, a xenon lamp, or the like.
[0131] The wavelength of the active energy ray is preferably 200 to 400 nm, more preferably 350 to 400 nm. The amount of irradiation is usually an illuminance of 50 to 1,000 mW / cm. 2 , light intensity 50~5,000mJ / cm 2 , preferably 1,000 to 5,000 mJ / cm 2 The irradiation time is usually 0.1 to 1,000 seconds, preferably 1 to 500 seconds, and more preferably 10 to 100 seconds. In order to satisfy the above-mentioned light amount in consideration of the heat load in the light irradiation step, irradiation may be performed multiple times.
[0132] In this case, in order to prevent deterioration of the polymer component (A) due to the irradiation of active energy rays and coloring of the cured resin layer, the curable resin composition may be irradiated with active energy rays through a filter that absorbs light of wavelengths unnecessary for the curing reaction. According to this method, the light of wavelengths unnecessary for the curing reaction and that deteriorate the polymer component (A) is absorbed by the filter, so that deterioration of the polymer component (A) is suppressed and a colorless and transparent cured resin layer is easily obtained. As the filter, a resin film such as a polyethylene terephthalate film can be used. When a resin film is used, it is preferable to provide a step of laminating a resin film such as a polyethylene terephthalate film on the curable resin layer between steps 1 and 2. The resin film is usually peeled off after step 2.
[0133] The curable resin layer can also be cured by irradiating the curable resin layer with an electron beam. When irradiating with an electron beam, the curable resin layer can usually be cured without using a photopolymerization initiator. When irradiating with an electron beam, an electron beam accelerator or the like can be used. The irradiation dose is usually in the range of 10 to 1,000 krad. The irradiation time is usually 0.1 to 1,000 seconds, preferably 1 to 500 seconds, and more preferably 10 to 100 seconds.
[0134] The curing of the curable resin layer may be carried out under an inert gas atmosphere such as nitrogen gas, if necessary. By carrying out the curing under an inert gas atmosphere, it becomes easier to avoid oxygen, moisture, etc. from interfering with the curing.
[0135] 4. Manufacturing method of transparent conductive film The method for producing a transparent conductive film according to the embodiment of the present invention is preferably a method including the following steps 3 and 4. Step 3: Forming a conductive material layer on the cured resin layer of the laminate for transparent conductive film Step 4: Heating the conductive material layer obtained in step 3 to 140° C. or higher to form a transparent conductive layer.
[0136] The method for producing a transparent conductive film according to the embodiment of the present invention may include the following step 5. Step 5: A step of patterning the transparent conductive layer obtained in step 4 into a predetermined shape.
[0137] Fig. 4 shows an example of a manufacturing process of a transparent conductive film according to an embodiment of the present invention. Fig. 4(a) shows a laminate for a transparent conductive film before a conductive material is disposed. Fig. 4(b) corresponds to the above step 3, Fig. 4(c) corresponds to the above step 4, and Fig. 4(d) corresponds to the above step 5, respectively.
[0138] (Step 3) On the cured resin layer obtained in step 2, a conductive material layer (reference numeral 3a in FIG. 4(b)) is disposed. The conductive material layer can be formed by, for example, sputtering, EB deposition, ion deposition, etc. A PVD method such as a plating method or a CVD method can be used. A method of forming a conductive material layer by applying a composition containing a conductive material and a solution onto a cured resin layer and drying the composition can also be used. The conductive material layer is formed, for example, so as to cover the entire surface of the cured resin layer.
[0139] (Step 4) In step 4, the conductive material layer formed in step 3 is heated to 140° C. or higher to crystallize the conductive material, thereby forming a transparent conductive layer (reference numeral 3 in FIG. 4(c)). In this manner, a transparent conductive film 20 is obtained. The conductive material layer may be heated by an electric furnace or the like.
[0140] The transparent conductive layer can be formed by various methods, but it is necessary to perform heating to crystallize the conductive material layer. In addition, when the conductive material layer is formed by coating, it is necessary to heat and dry the composition containing the conductive material after coating it. As described above, the cured resin layer according to the embodiment of the present invention has an absolute value of the thermal deformation rate at a temperature rise of 150° C. of 1.2% or less, and is therefore not easily affected by heating when forming the transparent conductive layer.
[0141] By continuously forming a conductive material layer on the cured resin layer and heating the conductive material layer while transporting a long process film on which a cured resin layer has been formed in a fixed direction, a long laminate in which a transparent conductive layer has been formed on the cured resin layer can be efficiently produced.
[0142] (Step 5) In step 5, a transparent conductive layer patterned into a desired shape (reference numeral 31 in FIG. 4(d)) is formed by removing a portion of the transparent conductive layer formed in step 4. Through step 5, a transparent conductive film 21 having a patterned transparent conductive layer is obtained. Methods for patterning the transparent conductive layer include, for example, masking the portions corresponding to the desired shape and then contacting the transparent conductive layer with an etching solution to partially remove the transparent conductive layer, or removing unnecessary portions by irradiating with a laser. In addition, a transparent conductive layer having a desired pattern shape may be formed on the cured resin layer without going through a process such as etching by selectively placing a transparent conductive material on the cured resin layer and heating it to form a transparent conductive layer.
[0143] After obtaining the transparent conductive film by the above steps, an adhesive layer may be provided on the transparent conductive layer. As is clear from the above description, the transparent conductive film obtained by the above production method is thin, has excellent heat resistance, excellent transparency and optical isotropy, and the transparent conductive layer has good electrical properties. EXAMPLES
[0144] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.
[0145] Measurement and evaluation of physical properties of the cured resin layer and the laminate for a transparent conductive film in each of the Examples and Comparative Examples were performed according to the following procedures.
[0146] <Measurement of thermal deformation rate of cured resin layer> The first polyethylene terephthalate (PET) film on the cured resin layer side, which corresponds to the process film, was peeled off and removed, and four cured resin layers were laminated to a thickness of 20 μm. Next, the test pieces were cut into 5 mm × 30 mm test pieces, and the laminate of the cured resin layers was held by setting the chuck distance to 20 mm using a thermomechanical analyzer (TMA4000SE manufactured by Netsch Japan Co., Ltd.). Next, the laminate of the cured resin layers was heated from 25 ° C to 150 ° C at 5 ° C / min, and then cooled to 25 ° C at 5 ° C / min. The rate of change in displacement in the longitudinal direction before and after heating (a value showing the ratio of the amount of displacement to the chuck distance of 20 mm as a percentage) was taken as the thermal deformation rate of the cured resin layer. In addition, the case where the laminate of the cured resin layer contracted was taken as a negative value, and the case where it expanded was taken as a positive value.
[0147] <Breaking elongation of cured resin layer> The cured resin layer was cut into a test piece of 15 mm × 150 mm, and the breaking elongation was measured according to JIS K7127:1999. Specifically, the test piece was attached to a tensile tester (Shimadzu Corporation, Autograph) with the chuck distance set to 100 mm, and a tensile test was performed at a speed of 200 mm / min to measure the breaking elongation [%]. If the test piece did not have a yield point, the tensile breaking strain was regarded as the breaking elongation, and if it had a yield point, the strain at the yield point was regarded as the breaking elongation.
[0148] <Removability of processing film in laminate for transparent conductive film> After peeling off the second process film of the laminate for transparent conductive film (width 50 mm), the first process film (first PET film in Examples 1, 2, Comparative Examples 1 to 3, biaxially stretched polyester film in Comparative Example 4) was peeled off at a peeling angle of 180° and a peeling speed of 0.3 m / min using a Tensilon universal testing machine RTG-1225 (A&D Co., Ltd.) in accordance with JIS Z0237:2000, and the appearance change of the laminate for transparent conductive film after the test was evaluated. The peeling test was performed by bonding the surface of the cured resin layer exposed by peeling off the second process film to a glass plate with a double-sided adhesive film, and then peeling off the first process film. The case where there was no change in the shape of the cured resin layer was evaluated as pass ("A"), and the case where there was a change in shape was evaluated as fail ("B").
[0149] [Example 1] A curable resin composition 1 for forming a cured resin layer was prepared by the following procedure. As a polymer component, 100 parts by mass of polyimide resin (PI) pellets (Kawamura Sangyo Co., Ltd., product name KPI-MX300F, Tg = 354 ° C., weight average molecular weight 280,000) were dissolved in methyl ethyl ketone (MEK) to prepare a 15% by mass solution of PI. Next, 122 parts by mass of tricyclodecane dimethanol diacrylate (Shin-Nakamura Chemical Co., Ltd., A-DCP) as a curable monomer and 5 parts by mass of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (BASF, Irgacure 819) as a polymerization initiator were added to this solution and mixed to prepare a curable resin composition 1. Note that the curable monomers and polymerization initiators used in this example and other experimental examples do not contain solvents and are all raw materials with a solid content of 100%.
[0150] Next, a first PET film (Toyobo Co., Ltd., Cosmoshine PET100A-4160, thickness 100 μm) having an easy-adhesion layer on one side was used as the first process film, and a curable resin composition was applied to the side of this PET film opposite the easy-adhesion layer, and the coating was dried by heating at 90°C for 3 minutes. Furthermore, a second PET film (Toyobo Co., Ltd., Cosmoshine PET50A-4160, thickness 50 μm) having an easy-adhesion layer on one side was laminated as a second process film on the dried coating film so that the surface opposite to the easy-adhesion surface was facing the above-mentioned. Then, using a belt conveyor type ultraviolet irradiation device (I-Graphics Co., Ltd., product name: ECS-401GX), ultraviolet lamp height 100 mm, ultraviolet lamp output 3 kW, light wavelength 365 nm illuminance 400 mW / cm 2 , light intensity 800mJ / cm 2 The resin was irradiated with ultraviolet light through the second PET film under the conditions of 25° C. (measured with an ultraviolet actinometer UV-351 manufactured by ORC Manufacturing Co., Ltd.) to carry out a curing reaction, forming a cured resin layer with a thickness of 5 μm, and a laminate for a transparent conductive film was obtained.
[0151] [Example 2] A laminate for a transparent conductive film was obtained in the same manner as in Example 1, except that the curable monomer was changed to a combination of the above-mentioned tricyclodecane dimethanol diacrylate and a cyclizable polymerization monomer (FX-AO-MA, manufactured by Nippon Shokubai Co., Ltd.) (mixture ratio 1:1).
[0152] [Example 3] A laminate for a transparent conductive film was obtained in the same manner as in Example 1, except that the total amount of the curable monomer was the same cyclizable polymerizable monomer as that used in Example 2.
[0153] [Comparative Example 1] A laminate for a transparent conductive film was produced in the same manner as in Example 1, except that, as the polymer component, pellets of polysulfone resin (PSF) (ULTRASON S6010, manufactured by BASF, Tg = 187 ° C.) were used instead of pellets of polyimide resin (PI).
[0154] [Comparative Example 2] A methyl ethyl ketone solution of a polyimide resin was prepared in the same manner as in Example 1, except that a curable monomer and a polymerization initiator were not added, to obtain a resin composition 2. Then, using the resin composition 2, a simple resin layer, not a cured resin layer, was formed in the same manner as in Example 1, except that ultraviolet irradiation was not performed, to obtain a laminate for a transparent conductive film.
[0155] The measurement results for each of the examples and comparative examples are shown in Table 1.
[0156] [Table 1]
[0157] As is clear from Table 1, in Examples 1 to 3, by using a process film that contained a highly heat-resistant polymer component, a cured resin layer made of a curable monomer, and no release layer, it was possible to peel the process film (first PET film) from the cured resin layer having a thickness of 10 μm or less without any problems. In Comparative Example 1, the casting film (first PET film) could be peeled off from the cured resin layer having a thickness of 10 μm or less without any problems, but the cured resin layer had a large thermal deformation rate and was not suitable for the transparent conductive layer forming process. In Comparative Example 2, since no curable monomer was contained, the second process film could not be peeled off, and therefore the peelability could not be evaluated. [Explanation of symbols]
[0158] 1, 1A, 1B: Processing film 2: Cured resin layer 2a: Curable resin layer (cured resin layer before curing) 3: Transparent conductive layer 3a: Conductive material layer 10A, 10B: Laminate for transparent conductive film 20: Transparent conductive film 21: Transparent conductive film with a patterned transparent conductive layer 31: Patterned transparent conductive layer
Claims
1. A laminate for a transparent conductive film used to form a transparent conductive film, A process film and a cured resin layer are provided in this order, the cured resin layer is a layer made of a cured product of a curable resin composition containing a polymer component (A) and a curable monomer (B), the absolute value of the thermal deformation rate of the cured resin layer due to a temperature rise of 150° C. is 1.2% or less; The thickness of the cured resin layer is 20 μm or less, The process film has a first surface which may be provided with a release layer and a second surface which is not provided with a release layer; The cured resin layer is formed on a second surface of the process film.
2. The laminate for a transparent conductive film according to claim 1 , wherein the polymer component (A) has a glass transition temperature of 250° C. or higher.
3. 3. The laminate for a transparent conductive film according to claim 1, wherein the polymer component (A) has a weight average molecular weight of 100,000 or more.
4. The laminate for a transparent conductive film according to any one of claims 1 to 3, wherein the polymer component (A) is a polyimide resin.
5. The laminate for a transparent conductive film according to claim 4 , wherein the polyimide resin is soluble in methyl ethyl ketone.
6. The laminate for a transparent conductive film according to claim 4 , wherein the polyimide resin has a fluoro group in a molecule.
7. The laminate for a transparent conductive film according to any one of claims 1 to 6, wherein the cured resin layer has a breaking elongation of 2.5% or more.
8. A transparent conductive film comprising: the laminate for a transparent conductive film according to any one of claims 1 to 7; and a transparent conductive layer provided on the cured resin layer of the laminate for a transparent conductive film.
9. A method for producing a transparent conductive film, comprising: forming a conductive material layer on the cured resin layer of the laminate for a transparent conductive film according to any one of claims 1 to 7; and heating the conductive material layer to 140°C or higher to form a transparent conductive layer.
Citation Information
Patent Citations
Dry film for protective film formation and fabricated article using same
JP2007293001A
Transfer film, electrode protective film, laminate, capacitive input device, and method for manufacturing transfer film
JP2018024225A
Transfer film, electrode protective film, laminate, capacitive input device, method for manufacturing capacitive input device, and method for manufacturing transfer film
JP2018024226A
Laminate, flexible device, and method for producing laminate
JP2018122583A
Polyimide powder and method for producing same
WO2017179367A1
